Effect of neonatal or adult heat acclimation on plasma fT3 level, testicular thyroid receptors expression in male rats and testicular steroidogenesis in vitro in response to triiodothyronine treatment - B. Kurowicka; M. Chrusciel; A. Zmijewska; G. Kotwica (Polish Academy of Sciences, 2026)
This study aimed to evaluate the effect of heat acclimation of neonatal and adult rats on their testes response to in vitro treatment with triiodothyronine (T3). Four groups of rats were housed from birth as: 1) control (CR) at 20°C for 90 days, 2) neonatal heat-acclimated (NHA) at 34°C for 90 days, 3) adult heat-acclimated (AHA) at 20°C for 45 days followed by 45 days at 34°C and 4) de-acclimated (DA) at 34°C for 45 days followed by 45 days at 20°C. Blood plasma and both testes were harvested from 90-day old rats. Testicular slices were then submitted to in vitro treatment with T3 (100 ng/ml) for 8 h. Plasma fT3 level was lower in AHA, NHA and DA groups than in CR group. Basal thyroid hormone receptor α1 (Thra1) expression was higher in testes of NHA and DA and β1 receptor (Thrb1) in DA rats vs. other groups. In the in vitro experiment, T3: 1) decreased Thra1 expression in all groups and Thrb1 in DA group, 2) increased Star expression in CR, NHA and DA groups, and Hsd17b3 expression in NHA group, 3) decreased the expression of Cyp11a1 in NHA and DA groups, and Cyp19a1 in all the groups, 4) did not affect the activity of steroidogenic enzymes and steroid secretion (A4, T, E2) in all the groups. These results indicate, that heat acclimation of rats, depending on their age, mainly affects the testicular expression of steroidogenic enzymes in response to short-lasting treatment with T3.